2017
DOI: 10.1016/j.ijfoodmicro.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Drying and decontamination of raw pistachios with sequential infrared drying, tempering and hot air drying

Abstract: Pistachio nuts have been associated with outbreaks of foodborne disease and the industry has been impacted by numerous product recalls due to contamination with Salmonella enterica. The current hot air drying of pistachios has low energy efficiency and drying rates, and also does not guarantee the microbial safety of products. In the study described herein, dehulled and water-sorted pistachios with a moisture content (MC) of 38.14% (wet basis) were dried in a sequential infrared and hot air (SIRHA) drier to <9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In our study, the highest IV values were found for Ordu Levant hazelnuts (94.69-94.91) while the lowest values were recorded for Tombul cultivar (92.96-93.96), and also, in generally, it is known that IV value varies according to cultivars. Our study demonstrated that the effect of the four drying methods on IV value was statistically significant (p \ 0.001; Tavakolipour et al (2010) and Venkitasamy et al (2017), the rise in drying temperature was observed to lead to an increase in FFA values. However, Kashaninejad et al (2003) reported that drying methods did not affect FFA values in pistachios.…”
Section: Oxidation Of Oilmentioning
confidence: 59%
See 1 more Smart Citation
“…In our study, the highest IV values were found for Ordu Levant hazelnuts (94.69-94.91) while the lowest values were recorded for Tombul cultivar (92.96-93.96), and also, in generally, it is known that IV value varies according to cultivars. Our study demonstrated that the effect of the four drying methods on IV value was statistically significant (p \ 0.001; Tavakolipour et al (2010) and Venkitasamy et al (2017), the rise in drying temperature was observed to lead to an increase in FFA values. However, Kashaninejad et al (2003) reported that drying methods did not affect FFA values in pistachios.…”
Section: Oxidation Of Oilmentioning
confidence: 59%
“…Fu et al (2016) and Qu et al (2016) also reported that PV increased due to the extended time of sun-drying. Furthermore, Venkitasamy et al (2017) reported that the PV in Kerman pistachio increased in parallel to the increase in drying temperature (0.80-1.87 meq O 2 kg -1 ). In general, decreases RV and increases of FFA, PV and IV values and corresponding decreases of O/L values were recorded.…”
Section: Oxidation Of Oilmentioning
confidence: 99%
“…The impact of hot air-drying technology on quality attributes of foods has been studied in recent years. For instance, the changes of lipid composition and oxidation in pistachios, the effect of volatile components of the enoki mushroom as well as the physicochemical properties and biological activity of mushroom polysaccharides induced by hot air drying have been studied [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent drying is a process by which drying conditions are changed with time (Kingsly, 2007;Kumar et al, 2014) by performing drying and tempering stages sequentially. For all drying methods, tempering is widely considered a significant procedure and has been proven to have positive effects on paddy rice drying (Sacchetti et al, 2005;Igathinathane et al, 2008;Venkitasamy et al, 2017;Wang et al, 2017). Studies have shown that temperature, time and the intermittent ratio all affect the tempering effects of paddy rice drying (Shei & Chen, 1998;Cnossen et al, 2003;Ng et al, 2005).…”
Section: Introductionmentioning
confidence: 99%